Unsaturated traffic oriented spatial clustering multiusers MAC protocol for the next generation WLAN. Issue 2 (3rd July 2021) - Li, Yong; Li, Bo; Yang, Mao
The next generation Wireless Local Area Network (WLAN) needs to significantly improve area throughput in high-dense deployment scenarios. Facing to the interference spread problem of OFDMA MAC, some existing studies introduce Spatial Clustering Group-based OFDMA (SCG-OFDMA) protocol, which enables geographically close nodes to send uplink OFDMA data simultaneously. However, SCG-OFDMA assumes that all the nodes have saturated traffic, which cannot be directly extended to the unsaturated traffic case. In this paper, an unsaturated traffic oriented Spatial Clustering Multiusers MAC (SCM-MAC) protocol is proposed. Specifically, Spatial Clustering Multiusers (SCM) discovery process is designed. After that, whether the cluster heads have traffic or not, they contend channel for their group members. Moreover, theoretical analysis of the optimal access radius is derived. Simulation results are in agreement with the theoretical analysis, and show that the area throughput of SCM-MAC is 34% and 50% higher than that of IEEE 802.11ax and OMAX protocol, respectively.